Marginal integrity of aesthetic restorations following intracoronal bleaching with sweet potato extract as an additive: An SEM study. Issue 2 (February 2020) - Ishwarya, Gurucharan; Vidhya, Sampath; Mahalaxmi, Sekar
Abstract: The aim of this in vitro study was to evaluate the marginal integrity of an alkasite restoration in comparison to that of a conventional composite resin restoration following intra-coronal bleaching with 30% hydrogen peroxide (HP) containing sweet potato extract (SPE) as an additive. Access cavities were prepared in 60 extracted human incisors. The teeth were decoronated 2mm below the CEJ and the pulp chambers were sealed cervically. The samples were divided into two groups (n = 30) based on the type of restorative material - group I: Hybrid composite resin and group II: Alkasite restorative material. Both the groups were divided into three subgroups (n = 10) based on the intra-coronal bleaching agent used namely, subgroup A: no bleaching (NB); subgroup B: 30% hydrogen peroxide (HP) and subgroup C: 30% hydrogen peroxide containing SPE (HSP). The tooth-restorative interface was observed under a scanning electron microscope (SEM) to determine the marginal integrity. The results were tabulated and statistically analyzed using one-way ANOVA. Specimens bleached with HP alone showed higher marginal gaps, irrespective of the restorative material used. Subgroups A and C showed lesser marginal gaps under both the restorative materials. An improved marginal integrity was seen with the alkasite material. It can be concluded that the addition of SPE to HP improves the marginal integrity of the coronal restorative material placed immediately post-bleaching. The new alkasite material holds promise as a permanent coronal seal in cases of intra-coronal bleaching. Abstract : Dentistry; Materials science; Materials application; Natural product chemistry; Material science of foods; Alternative medicine; Antioxidant; Bleaching; Catalase; Marginal seal; Reactive oxygen species; Sweet potato